“There were banquets and parties every day”: the importance of British female circles for the Serbian Enlightenment (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper deals with the important influence of the British female circles on the main figure of the Serbian Enlightenment – Dositej Obradović. When Obradović arrived in England in 1784, he had the opportunity to frequent the Scottish community in London and to get acquainted with Mrs. Livie and her sister Mrs. Taylor who participated actively in the British cultural life of the day. It was those women who advised him about the titles of the recently published books, about the authors, and about the current topics of interest. They also suggested that he should translate the stories of Elizabeth Carter and Anna Laetitia Barbauld, two very popular figures of the British Enlightenment.
Keywords: Dositej Obradović; British female circles; British Enlightenment; Scottish Enlightenment